Matrimonial property: the causes of claim and distribution rate - Dahaman@Dahlan, Mohd Akram; Nawawi, Khairani; Mohd Diah, Muhammad Fadhli (Future Academy, 2018)
Matrimonial property is a form of property division that is practiced by the Malaysian Muslim community based on the custom of people in the Nusantara. In Kedah there are two issues that need to be examined which are; the reason of matrimonial property and rate of equitable division. A study in the form of content analysis is conducted on cases that were listed and discussed in the Syariah High Court, Alor Setar starting from 2011 to 2013. Based on the analysis, there are three conditions that lead to matrimonial property claim. The causes are divorce, the death of a spouse and polygamous marriages. Based on the analysis made, it is shown that all three conditions have been given a strong base by the Syariah High Court for a claim to be a case. Whereas in connection with the claim, there are three rates as the solution to a matrimonial property claim which are 1/2: 1/2, 1/3, 2/3 and 3/4: 1/4. These divisions are made by looking at the facts and evidence of contributions of both the husband and wife, directly or indirectly. Based on the analysis made, it is shown that all three of rates have been applied by the Syariah High Court to resolve all cases billed in this Court.